Mapping the knowledge of research trends in sports performance asymmetries from 2015 to 2024: a bibliometric study and analysis of the most-cited papers - Becerra-Patiño, B. A.; Paucar-Uribe, J. D.; Olivares-Arancibia, J.; Ojeda-Aravena, A.; Yáñez-Sepúlveda, R.; Gamonales, J. M.; López-Gil, J. F.; Hernández-Beltrán, V. (Sports, 2025)
In recent years, studies related to preventing injuries and improving sports performance have aroused academic interest. However, no bibliometric study has investigated asymmetry. The aim of this study was twofold: (i) to identify trends in research on asymmetries in sports performance through bibliometric analysis, and (ii) to determine the most-cited articles to establish the main lines of research on asymmetries. The final sample consisted of 471 documents. The results show that, during the publication period, there was a considerable increase (73%) in research between 2020 and 2021, with 2022-2023 being the year with the highest production and number of citations. Most of the publications consisted of research articles (93.41%), with a low percentage of review studies (4.24%). The Journal of Strength and Conditioning Research and Symmetry were the journals with the highest number of documents (n = 57) and citations (n = 1230). The journals that produced the most knowledge were those in the first quartile (Q1) and the second quartile (Q2). The most prolific author was Bishop, C. The countries with the highest number of published documents were England (140 documents and 3039 citations) and the United States (94 documents and 2099 citations). The most common words in the studies were performance (n = 162), strength (n = 167), reliability (n = 118), injury (n = 94), and asymmetry (n = 90). The study of asymmetries in sports performance has focused on two main approaches: one related to analyzing differences between limbs, and the other focused on assessing strength after postoperative processes. The analysis of the existing body of knowledge on asymmetries allows us to incorporate the latest scientific advancements. In turn, this helps us to establish best practices to enhance both sports performance and rehabilitation processes.